On the need to develop nuanced measures assessing attitudes towards AI and AI literacy in representative large-scale samples - Christian Montag (413788) (2024)
Since the launch of the generative AI, including tools such as ChatGPT, the impact of artificial intelligence (AI) on societies has been extensively discussed. How far reaching will the impact of AI be? On the positive side, AI might help find solutions for the world’s problems, such as tackling issues around climate change or the development of new psychopharmaceuticals to enhance global mental health. However, AI, as a technology that leads to more automation in many areas, might also cause job loss or can do harm in other ways. Other Information Published in: AI & SOCIETY License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00146-024-01888-1